Trust and mistrust in COVID-19 politics: the shattered hopes of civil society engagement in Burkina Faso - Guiatin, Jean-Baptiste (Frontiers in Political Science, 2024)
In a democratic setting, civil society is considered to be one of the forces capable of checking on the government especially when it comes to issues that concern the public at large. The political history of Burkina Faso is replete with situations of civil society groupings confronting the governments be they democratic or authoritarian. So, at the outbreak of the COVID-19 pandemic in March 2020 in Burkina Faso one expected civil society organizations to live up to the challenges of the day by checking on the actions of President Kabore government. However, this did not happen. Hence, the following research question: Why was the Burkina Faso civil society inactive during the COVID-19 pandemic crisis? Using elite interviewing techniques, I found out that low awareness of the COVID-19 threat within large swaths of the population and among members of civil society organizations accounted for the inaction of the most vocal civil society members during the COVID-19 pandemic crisis since the latter did not consider the COVID-19 pandemic issue as a political question deserving great attention. This has strong implications in terms of public trust. More precisely, it means that in Burkina Faso contrary to what the democracy promotion literature may have said on the virtues of civil society one cannot always trust civil society members to check on the government even in time of emergency such as that of the COVID-19 pandemic crisis. Further research may therefore help to better understand civil society-government relations in Burkina Faso.